The Effect of Population Density on The Risk of Tuberculosis in Densely Populated Environments - Aulia, Khansa Tsabitah; Yuniati, Shinta Karina; Seto, Andreas Aryo Bayu (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Background: Tuberculosis (TB) remains a significant global health challenge, with Indonesia ranking second globally in the number of Tuberculosis cases after India. High population density, particularly in slum areas with poor sanitation, plays a crucial role in facilitating TB transmission. These unhealthy environmental conditions significantly elevate transmission risks, especially in communities struggling with poverty. Objectives: This study aims to evaluate the relationship between population density and the risk of TB transmission in overcrowded neighborhoods. Methods: A literature review was conducted on studies published between 2019 and 2024, utilizing keywords related to tuberculosis, population density, and densely populated settlements. Results: High population density, especially in areas characterized by substandard housing and inadequate ventilation, substantially increases the risk of TB transmission. Conclusion: Overcrowded neighborhoods with poor housing conditions significantly contribute to the spread of TB. Addressing these issues through improved housing and sanitation is essential to reduce transmission rates and protect public health.